Application of innovative space technology approaches to the sustainability of agricultural systems in the developing world. Issue 4 (3rd April 2021) - Lamba, Shubham; Rani, Savita; Kumar, Neeraj
ABSTRACT: The climate change is severely impacting global agriculture, especially that of the developing world where non-availability/awareness of advanced technologies at the root level is a significant limitation. Adopting advanced and sustainable technologies, such as space technologies can be a successful approach in minimizing the severe impacts as evident from the developed first-world nations that have shown successful and sustainable applications of these technologies. This manuscript inculcates some of those crucial applications that can be adopted in the developing world's agricultural production systems. The valued information could be instrumental to scientific and non-scientific readers in facilitating extensive awareness and adoption of these state-of-the-art technologies.